Antimicrobial Photodynamic Inactivation: An Alternative for Group B Streptococcus Vaginal Colonization in a Murine Experimental Model - Michał K. Pierański; Jan G. Kosiński; Klaudia Szymczak; Piotr Sadowski; Mariusz Grinholc (MDPI AG, 2023)
Background: Streptococcus agalactiae, referred to as Group B Streptococcus (GBS), is a prominent bacterium causing life-threatening neonatal infections. Although antibiotics are efficient against GBS, growing antibiotic resistance forces the search for alternative treatments and/or prevention approaches. Antimicrobial photodynamic inactivation (aPDI) appears to be a potent alternative non-antibiotic strategy against GBS. Methods: The effect of rose bengal aPDI on various GBS serotypes, Lactobacillus species, human eukaryotic cell lines and microbial vaginal flora composition was evaluated. Results: RB-mediated aPDI was evidenced to exert high bactericidal efficacy towards S. agalactiae in vitro (>4 log10 units of viability reduction for planktonic and >2 log10 units for multispecies biofilm culture) and in vivo (ca. 2 log10 units of viability reduction in mice vaginal GBS colonization model) in microbiological and metagenomic analyses. At the same time, RB-mediated aPDI was evidenced to be not mutagenic and safe for human vaginal cells, as well as capable of maintaining the balance and viability of vaginal microbial flora. Conclusions: aPDI can efficiently kill GBS and serve as an alternative approach against GBS vaginal colonization and/or infections.